2018
DOI: 10.1029/2017ja024883
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sodium Layers: Their Appearance and Disappearance

Abstract: Temperature variation has been proposed to play an important role in the formation of the sporadic sodium layers (SSLs or Na S ) in subtropic area, based on the observed significant correlation between SSLs and high temperatures. The icy-dust particle, which could form in the extremely cold conditions and act as absorbers of sodium species, was proposed to be a possible candidate for the sodium reservoir of the SSLs. In this study, the University of Science and Technology of China temperature/wind lidar and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
(146 reference statements)
0
3
1
Order By: Relevance
“…Moreover, the other LTSL on 4 May 2014, a large temperature enhancement was also present, the temperature raised from 206 K to 277 K at 105 km from 19:30 LT to 21:25 LT. However, the lowest temperature was 169 K at 102 km, is higher than previous reported extremely cold phase 150 K [40] for ice dust. Although tidal waves or other such reasons can have amplitude of 40-60 K in the MLT region.…”
Section: The Correlation Between Ltsls and Escontrasting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the other LTSL on 4 May 2014, a large temperature enhancement was also present, the temperature raised from 206 K to 277 K at 105 km from 19:30 LT to 21:25 LT. However, the lowest temperature was 169 K at 102 km, is higher than previous reported extremely cold phase 150 K [40] for ice dust. Although tidal waves or other such reasons can have amplitude of 40-60 K in the MLT region.…”
Section: The Correlation Between Ltsls and Escontrasting
confidence: 66%
“…The temperature-controlled theory was first proposed by Zhou et al, which suggested the triggering of sodium atoms by some means through temperature enhancement in a narrow altitude region due to energy damping during gravity wave breaking [39]. Recently, an empirical model was proposed that sodium species were collected by an icy-dust reservoir and stored during the extremely cold phase (<150 K) and a large temperature enhancement (>40 K of temperature increase) triggered a generation of sodium atoms [40]. Therefore, we turn to the temperature profiles from SABER.…”
Section: The Correlation Between Ltsls and Esmentioning
confidence: 99%
“…The sporadic E (E s ) layers, thin layers of concentrated metallic plasma in the lower E region of the ionosphere, are proposed to be a source of sodium in the mesosphere . Studies show that the SSLs are closely related to the changes in Na + metallic ions within E s layers (Yuan et al, 2014b;Qiu et al, 2018;Cai et al, 2019a, b;Xia et al, 2021). From a laboratory kinetic study, Cox and Plane (1998) demonstrated that the sporadic metal layer is produced when the E s layer descends below 100 km under the influence of tides.…”
Section: Introductionmentioning
confidence: 99%
“…The other candidates for the source of sodium atoms could be direct meteor deposition, and/or release from aerosol particles, as well as redistribution of existing atoms (e.g., Batista et al, 1991;Clemesha, 1995;Clemesha et al, 1978). However, direct meteor deposition requires a meteor shower with a large mass, and aerosol particle release requires a background temperature increase (Qiu et al, 2015(Qiu et al, , 2018. The redistribution of existing atoms is another good explanation for SSLs.…”
mentioning
confidence: 99%